Measurement properties of the Rajka–Langeland severity score in children and adults with atopic dermatitis. (1st January 2021) - Silverberg, J.I.; Lei, D.; Yousaf, M.; Janmohamed, S.R.; Vakharia, P.P.; Chopra, R.; Chavda, R.; Gabriel, S.; Patel, K.R.; Singam, V.; Kantor, R.; Hsu, Derek Y.
Summary: Background: Multiple atopic dermatitis (AD) severity scales exist, with no gold standard for use in clinical practice. Objectives: To determine the measurement properties of the Rajka–Langeland score and compare it with other clinician‐reported outcomes in adults and children with AD. Methods: We performed a prospective dermatology practice‐based study using questionnaires and evaluation by a dermatologist ( n = 427). Results: Rajka–Langeland had good concurrent validity with the Eczema Area and Severity Index (Spearman rho = 0·63), SCORing AD (SCORAD) (rho = 0·61), objective‐SCORAD (rho = 0·52) and body surface area (rho = 0·51); good convergent validity with the numeric rating scale average‐itch (rho = 0·60) and worst‐itch (rho = 0·59), Patient‐Oriented Eczema Measure (rho = 0·57), Dermatology Life Quality Index (rho = 0·53), Patient‐Reported Outcomes Measurement Information System Itch Questionnaire (rho = 0·35–0·55) in adults and/or children; fair discriminant validity for patient‐ and physician‐reported global AD severity; good responsiveness to change of severity of AD and itch; good reliability; internal consistency; with no floor or ceiling effects. Interpretability bands (3, clear/almost clear; 4–5, mild; 6–7, moderate; 8–9, severe) and minimal clinically important difference (1 point) were established. Conclusions: The Rajka–Langeland score showed good construct validity, reliability, internal consistency and responsiveness in adults and children with AD.